Langkah-langkah Evaluasi Pembelajaran - Nur Aidila Fitria; Muhammad Yoga Julyanur; Eka Widyanti (PUSTAKA: Jurnal Bahasa dan Pendidikan, 2024)
Learning is a process that aims. Learning objectives that are to be achieved well, of course, should take good ways or steps in knowing the success of students' learning. The extent to which students understand the learning material can only be known by conducting a learning evaluation process. This research is a literature study type research, in which the author collects materials related to the research, both from books, journals, literature, and other publications that are relevant and can be used as sources for further research by the author. As a result, learning evaluation is an assessment carried out by an educator of the extent to which students understand the learning that has been conveyed in teaching and learning activities in order to improve and improve the quality of learning. The types of evaluation such as placement, formative, diagnostic, and summative evaluation play an important role in helping educators and students to achieve the desired learning goals and outcomes. Then, determining the purpose of the evaluation, selecting the evaluation design, validating the data, processing and interpreting the data, providing interpretation and drawing conclusions, and carrying out follow-up evaluation are the steps in the learning evaluation process. Finally, a good evaluation must fulfill characteristics such as validity, objectivity, practicality, and economy in order to provide accurate information and support quality decision-making in the learning process.